Dwarf and Increased Branching 1 controls plant height and axillary bud outgrowth in Medicago truncatula. (23rd September 2020) - Zhang, Xiaojia; He, Liangliang; Zhao, Baolin; Zhou, Shaoli; Li, Youhan; He, Hua; Bai, Quanzi; Zhao, Weiyue; Guo, Shiqi; Liu, Yu; Chen, Jianghua
Abstract : Dwarf and Increased Branching 1 ( DIB1 ), encoding the gibberellin 3 β -hydroxylase GA3ox1, controls plant height and axillary bud outgrowth in Medicago truncatula . Abstract: Optimizing plant architecture is an efficient approach for breeders to increase crop yields, and phytohormones such as gibberellins (GAs) play an important role in controlling growth. Medicago truncatula is a model legume species, but the molecular mechanisms underlying its architecture are largely unknown. In this study, we examined a tobacco retrotransposon Tnt1 -tagged mutant collection of M. truncatula and identified dwarf and increased branching 1 ( dib1 ), which exhibited extreme dwarfism and increased numbers of lateral branches. By analysis of the flanking sequences of Tnt1 insertions in different alleles of the tagged lines, we were able to clone DIB1. Linkage analysis and reverse screening of the flanking-sequence tags identified Medtr2g102570 as the gene corresponding to the DIB1 locus in the dib1 loss-of-function mutants. Phylogenetic analysis indicated that DIB1 was the ortholog of PsGA3ox1/Le in Pisum sativum . Expression analysis using a GUS-staining reporter line showed that DIB1 was expressed in the root apex, pods, and immature seeds. Endogenous GA4 concentrations were markedly decreased whilst some of representative GA biosynthetic enzymes were up-regulated in the dib1 mutant. In addition, exogenous application of GA3 rescued the dib1 mutant phenotypes. Overall, our results suggest that DIB1 controls plant height and axillary bud outgrowth via an influence on the biosynthesis of bioactive GAs. DIB1 could therefore be a good candidate gene for breeders to optimize plant architecture for crop improvement.